Diagnosing and treating haemothorax in dogs and cats. Issue 8 (4th October 2019) - Allerton, Fergus
Abstract : Background: Cases of haemothorax are seen in primary practice. Given the range of potential aetiologies, a structured approach to diagnosis is important. Aim of the article: This article reviews the causes of haemothorax and outlines the approach to diagnosing this condition in practice, as well as how to treat cases.